Assessing Environmental Awareness and Attitudes in Higher Education: A Comparison between Environmental and Non-Environmental Discipline - Lidiastuti, Arinda Eka; Purnawati, Wilda (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2023)
The research was on the environmental awareness and attitude of biology college students. The samples were 50 using purposive technique sampling. The research approach was quantitative descriptive. The study was recommended to describe environmental awareness and attitude. The study was also done to determine the level of awareness and environmental behavior of Biology college students.. Researchers employed the Environmental Awareness Test and the Environmental Attitude Scale, both created by Dr. Haseen Taj and Dr. K Yeshodara, to gauge participants' levels of environmental awareness. According to the findings of the Unpaired T-Test analysis, there is a difference in the attitudes and levels of environmental awareness between environmental students and non-environmental students. The p values for environmental awareness and environmental awareness are 0.049 and 0.024, respectively, less than 0.05.. Furthermore, this study paves the way for future research endeavors to investigate the underlying factors influencing environmental awareness and attitudes.